134k views
2 votes
Two functions are shown in the table below f(x) equals -X squared plus 4X +12 And G(x)

equals X +2

User Joss
by
5.1k points

1 Answer

5 votes

Answer:


x = -2; x = 5

Explanation:

Given


f(x) = -x^2 + 4x + 12


g(x) = x +2

Required

For what value of x is:
f(x) = g(x)


f(x) = g(x) implies that


-x^2 + 4x + 12 = x + 2

Collect like terms


-x^2 + 4x -x + 12 -2 = 0


-x^2 + 3x + 10 = 0

Expand


-x^2 + 5x-2x + 10 = 0

Factorize


-x(x - 5)-2(x - 5) = 0

Factor out x - 5


(-x - 2)(x - 5) = 0

Solve for x


-x - 2 = 0; x - 5 = 0

So:


x = -2; x = 5

User Alex Cohn
by
6.0k points